Program Aplikasi Penggajian pada PT Fitria Trans Tamara Banjarmasin - Muhammad Syahid Pebriadi; Heldalina; Ike Nur Safitri (Indonesian Journal of Applied Accounting and Finance, 2021)
This study aims to create a payroll application program at PT Fitria Tamara Banjarmasin. The problem in this study is that there are constraints from the payroll system which is still done manually so it takes a long time and if an error occurs it will require additional time. The method used in this study includes the stages of collecting data using a field study approach and library study which serves to obtain initial data related to payroll problems in the company, the stages of system analysis which function to generate information and analysis of needs for payroll problems, stages of system design (flow system, user interface, and output) which serves to translate the results of the system analysis into system design and the stages of system implementation which function to apply the results of the system design stage into an application program. The results of the research are in the form of a suggested system flow and a payroll application that helps in calculating employee salaries.